MINAT PEKEBUN DALAM PENGOLAHAN KOPI ARABIKA MENJADI GREEN BEAN DI KECAMATAN MARANCAR KABUPATEN TAPANULI SELATAN PROVINSI SUMATERA UTARA - Butarbutar, Yenny Laura; Astuti, Linda Tri Wira; Lubis, Imam Wahyudi (Institute of Computer Science (IOCS), 2024)
Interest of Planters in Processing Arabica Coffee into Green Beans in Marancar District, South Tapanuli Regency, North Sumatra Province. The aim of this study is to examine the level of interest of growers in processing Arabica coffee into green beans and the factors that influence growers' interest in processing Arabica coffee into green beans in Marancar District, South Tapanuli Regency from April to May 2024. Data collection methods namely interviews, observations, documentation, and questionnaires using questionnaires that have been tested for validity and reliability. The sample determination method uses proportional random sampling. Next, the data analysis method uses a Likert scale and multiple linear regression. The results of the study show that the level of interest of growers in processing Arabica coffee into green beans in Maranccar District is 83.48% in the high category. Furthermore, the results of multiple linear regression analysis show the factors that influence growers' interest in processing Arabica coffee into green beans in Marancar District, namely formal education, the role of instructors, selling prices, and marketing.